Relação entre o Programa de Descentralização Administrativa e Financeira e o Projeto Político-Pedagógico em uma escola de Brasília - DF - Rosário, Raquel Maria Vieira do (2018)
The present study is part of the Policy, Management, Financing and Evaluation of Education research line of the Postgraduate Program in Education (PPGE) Stricto Sensu of the Universidade Católica de Brasília (UCB). It has as its theme aspects of convergence between the financial and pedagogical management of the teaching units. The object of study is the materialization of the Political Pedagogical Project (PPP) through the Program of Administrative and Financial Decentralization (PDAF) in a public education institution of the Federal District (DF). The theoretical framework is based on Paro (2010), Veiga (2000), Secchi (2010), Peroni; Adrian (2004). Documentary research is based on the Federal Constitution of 1988, Law no. 9,394 / 96, the decrees establishing the PDAF in the Federal District, as well as decrees and minutes related to the PDAF. The empirical field was a school in the Federal District and the Regional Coordination of Teaching of the Pilot / Cruise Plan of the Secretary of State for Education of the Federal District (SEEDF). Semi-structured interviews were conducted with school officials and with a server of the Regional Coordination of Teaching of the Pilot / Cruise Plan. In the interpretation of the analyzes, a content analysis was carried out (BARDIN, 2011) with the objective of understanding the relationship between the school financing program and the Political-Pedagogical Project (2014-2017). The results of the research made it possible to verify that: (a) the link between the PDAF and the PPP occurs in a manner consistent with the legal norms of the Federal District, (b) the relation between the use of the PDAF to achieve PPP is understood (c) the resources of the PDAF are used for administrative, didactic-pedagogical materials and maintenance of the school space, (d) the non-recurrence of the transfer of resources impairs the acquisition of instruments and services registered in the PPP of the school.